2015
DOI: 10.1063/1.4927215
|View full text |Cite
|
Sign up to set email alerts
|

Real-time sensing of epithelial cell-cell and cell-substrate interactions by impedance spectroscopy on porous substrates

Abstract: Oxidized porous silicon (PS) is a common topographical biocompatible substrate that potentially provides a distinct in vitro environment for better understanding of in vivo behavior. But in the reported studies on oxidized PS, cell-cell and cell-substrate interactions have been detected only by fluorescent labeling. This paper is the first attempt to investigate real-time sensing of these interactions on HaCaT cells by label-free impedance spectroscopy on oxidized PS of two pore diameters (50 and 500 nm). One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
4
9
0
Order By: Relevance
“…The penetration depth of the solution within the pore is dependent on different parameters like hydrophilicity of the surface, friction (due to viscosity), gravity, applied electric field and the 'pressure forces' originating out of various sources and can be estimated from Computational Fluid Dynamics software Ansys-FLUENT. It has been already reported that for oxidized porous substrates of around 50nm diameter, the penetration depth is around 1µm [20] which indicates that in our fabricated sensor samples of 50-100nm thickness, the solution can reach the pore bottom. Thus the sensing performance is expected to depend primarily on varying surface roughness of the samples.…”
Section: Resultsmentioning
confidence: 85%
“…The penetration depth of the solution within the pore is dependent on different parameters like hydrophilicity of the surface, friction (due to viscosity), gravity, applied electric field and the 'pressure forces' originating out of various sources and can be estimated from Computational Fluid Dynamics software Ansys-FLUENT. It has been already reported that for oxidized porous substrates of around 50nm diameter, the penetration depth is around 1µm [20] which indicates that in our fabricated sensor samples of 50-100nm thickness, the solution can reach the pore bottom. Thus the sensing performance is expected to depend primarily on varying surface roughness of the samples.…”
Section: Resultsmentioning
confidence: 85%
“…To ensure that most of the field lines intersect the cellular layer on top, it is required that the medium should not reach the pore bottom. Estimation of medium penetration depth into the pore by computational fluid dynamics software has been reported earlier [18] which suggests the thickness selection of 8 µm and 1 µm for PS1 and PS2 substrates respectively. A distributed electrical model has been proposed for various stages of cell development after wounding.…”
Section: Analytical Model For Impedance Calculationmentioning
confidence: 83%
“…There are no reports of non-invasive electrical monitoring of wound healing phenomena on nano/micro structured surfaces. Recently, real time impedance monitoring has been performed on nano/micro porous silicon substrates to quantify the vital cellular attributes like cell-cell junction resistance, cell substrate separation, mean cell radius and others during the growth of keratinocytes (HaCaT) [18]. But there has been no attempt to study the wound healing process electrically even on porous silicon substrates.…”
Section: C1mentioning
confidence: 99%
See 2 more Smart Citations